Performance Comparison between Gain Scheduling PID and Fuzzy Mamdani Controllers for an Air Heating Module - Rizky Maulana Hendradi; Septiantar Tebe Nursaputro; Arief Rahman Hakim; Wahyu Sulistiyo (Politeknik Negeri Semarang, 2026)
This study compares the performance of Gain Scheduling Proportional–Integral–Derivative (GS-PID) control and Fuzzy Mamdani control applied to an air heating module. The system was implemented using an STM32 microcontroller and evaluated experimentally under temperature setpoints of 50 °C, 60 °C, 70 °C, and 80 °C. Performance was assessed based on dynamic response parameters, including rise time, overshoot, steady-state error (SSE), Integral of Absolute Error (IAE), Integral of Squared Error (ISE), and Integral of Time-weighted Absolute Error (ITAE). The experimental results show distinct characteristics between the Gain Scheduling PID (GS-PID) and Fuzzy Mamdani controllers under varying setpoints. The GS-PID controller exhibits a rise time of approximately 4.0–4.9 s with relatively small overshoot in the range of 1.18–2.87%, while maintaining a very low steady-state error of about 0.001–0.24%. In contrast, the Fuzzy Mamdani controller achieves a faster rise time of around 2.0–2.6 s at low to medium setpoints, which increases to approximately 5 s at higher temperatures. The overshoot produced by the Fuzzy Mamdani method ranges from 0–4.78%, decreasing as the setpoint increases, with zero overshoot observed at high setpoints due to incomplete setpoint tracking. Moreover, the Fuzzy Mamdani controller yields higher performance index values (IAE, ISE, and ITAE), indicating larger accumulated error over time. Overall, GS-PID control is more effective in ensuring steady-state accuracy and stability, whereas Fuzzy Mamdani control provides a faster transient response at lower operating temperatures.